Prevalence of long gun use in Maryland firearm suicides - Paul S. Nestadt; Kevin MacKrell; Alexander D. McCourt; David R. Fowler; Cassandra K. Crifasi (BMC, 2020)
Abstract Background Firearms account for the majority of US suicides, largely due to lethality and accessibility. Under Federal and Maryland law, long guns are less regulated than handguns which is a concern for increased suicide risk. This study uses Maryland data to ascertain the impact of long guns on suicides in the state. We hypothesize that the prevalence of long gun use among firearm suicides will be increased in rural and young populations. Methods This is a cross sectional study using police and medical examiner narratives to identify firearm type involved in all 3931 Maryland gun suicides from 2003 to 2018. Proportions of firearm suicides utilizing long guns were calculated. Urban-rural differences were determined using the National Center for Health Statistics' classification system. Logistic regression was used to calculate odds ratios of long gun to handgun suicides across the urban-rural spectrum, controlling for decedent demographics. Results From 2003 to 2018, 28.4% of Maryland gun suicides used long guns. The proportion of long guns used was highest in the most rural counties, where 51.6% of firearm suicides were by long gun, compared to 16.8% in the most urban counties. Long guns were disproportionately used by the young. For decedents 18 or younger, 44.6% used long guns, compared to 20.2% in those 65 or older. Compared to the most urban counties, firearm suicide decedents in the most rural counties were 3.74x more likely to use long guns (OR = 3.74; 95% CI 2.19, 6.40; p < .001) after adjusting for demographics, intoxication, and hunting season. Conclusions Long guns are used in a large proportion of Maryland firearm suicides, particularly in rural areas and disproportionately in youth suicides. Long guns must be considered as part of access to lethal means or policy strategies in efforts to reduce the burden of firearm suicide.